ANALYSIS OF THE CYCLICAL GROUND CUTTING - V. A. Nikolayev (Вестник СибАДИ, 2019)
Introduction. Rotary rippers are needed for cyclical cutting of the ground when the underlying layer and slopes of the roads are formed. Therefore, the general purpose of the research is the theoretical justification of the design and mode of rotary ripper’s parameters. Using the synthesis method, researches get only indicative results. In order to calculate the parameters of ground cutting, it is necessary to analyze the interaction of working bodies with the ground.Materials and methods. Based on the planned ways to reduce the cost of energy for cyclical cutting of the ground, the author developed the calculation method of the working body: the force of cutting the ground with the toe of the working body; the force necessary for the primary shift of the ground by the front surface of the working body; the total force of ground displacement by an active working body; the friction of the side surfaces of the working body on the ground during the rotation.Results. The author calculated the specific values in the process of rotation by using the developed method of determining the parameters of the cyclic ground cutting and basing on the accepted data. Moreover, the author constructed and approximated the graphs’ dependencies of ground cutting parameters of the rotor angle. In particular, there were dependencies: the force required to shift the ground by an active working body, the mass of the displaced ground, the acceleration of the displaced ground, the force needed to accelerate the displaced soil, the force of the ground’s impact on the side surface of the displaced ground wedge, the friction force displaced by the active working body of the ground wedge on the array of soil, the total force of the displacement of the ground by the active working body from the angle of the rotor when moving the unit at various transmissions II range of tractor HTP-17221.Discussion and conclusions. The method of calculating the forces of the ground cutting and calculating their specific values helps to determine the required rotational moment and power of the rotor drive.The author has read and approved the final manuscript. Financial transparency: the author has no financial interest in the presented materials or methods. There is no conflict of interest.